How do you feel at school? A cross-country comparative analysis of migrant adolescents’ school well-being - Dežan, Lucija; Sedmak, Mateja (Frontiers in Education, 2023)
Adolescents present a relevant stakeholder in international migrations since they comprise a large share of all migrants. Previous studies show that migration processes significantly affect the well-being of migrant adolescents. This article investigates how the school environment, with its pedagogical practices and interpersonal relationships established between migrant adolescents, their classmates, and teachers, affect migrant adolescents’ well-being. Our research draws on quantitative data collected as part of the MiCREATE project. The sample of migrant adolescents (N = 700) was surveyed in 45 schools in 6 countries: Austria, Denmark, Slovenia, Spain, Poland, and the United Kingdom. Results indicate that migrant adolescents like school and feel safe there, however, they tend to be more satisfied with relationships established with teachers than with peers. Furthermore, differences in self-perceived school well-being emerge when comparing countries with a longer tradition of high migration flows (Spain, Denmark, the United Kingdom) and those less experienced (Poland and Slovenia), although slight exceptions were detected. The results lead to the conclusion that schools that foster intercultural education and fulfilling interpersonal relationships are essential for school well-being of migrant adolescents and present an essential step toward successful integration of migrant youth.